Perfluorooctanoic acid–associated complement factor B upregulation and atrial fibrillation–related molecular alterations: integrated network toxicology, Mendelian randomization, molecular dynamics, and HL-1 cell analyses - Dan Li; Chuanfeng Bai; Jinping Zhao (Frontiers in Cardiovascular Medicine, 2026)
Background Perfluorooctanoic acid (PFOA) is a persistent environmental pollutant associated with cardiovascular dysfunction, but the molecular links between PFOA exposure and atrial fibrillation (AF) remain unclear. We aimed to prioritize a candidate mediator connecting PFOA with AF and examine its associated molecular effects in atrial cardiomyocytes. Methods PFOA-associated or computationally predicted genes from CTD, STITCH, and SwissTargetPrediction were integrated with AF-associated genes. Complement factor B (CFB) was evaluated using exploratory Mendelian randomization, public single-cell analysis, protein-interaction and enrichment analyses, molecular docking, a single 100-ns molecular dynamics trajectory, and HL-1 cell experiments. Cells were exposed to 25 μM PFOA for 48 h with or without CFB silencing, followed by qRT-PCR, Western blotting, immunofluorescence, and CCK-8 assays. Results CFB was the only shared candidate between the integrated PFOA-related target set and the filtered AF-associated gene set. Genetically predicted plasma CFB levels were positively associated with AF risk (odds ratio = 1.109, 95% confidence interval: 1.021–1.205; FDR-adjusted P = 0.015). Public single-cell data showed preferential basal CFB expression in cardiac fibroblast and stromal populations, with lower expression in cardiomyocytes. The predicted PFOA–CFB pose remained within the selected pocket during the sampled trajectory. In HL-1 cells, PFOA increased CFB mRNA and protein abundance, decreased CACNA1C transcript levels without significantly changing CACNA1C protein abundance, and increased KCNJ2 and NPPA expression. CFB silencing attenuated the PFOA-associated increases in KCNJ2 and NPPA, whereas CACNA1C showed no corresponding rescue pattern. CFB immunoreactivity was detected within cTnT-positive, PFOA-exposed HL-1 cells. Conclusion These findings prioritize CFB as a candidate molecule potentially associated with PFOA exposure and AF-related molecular alterations. They do not establish direct PFOA–CFB binding, functional complement activation, causality, electrical remodeling, or a functional AF phenotype.